MANAJEMEN PENDIDIKAN KARAKTER DI SMA - Hasibuan, Abdul Aziz; Syah, Darwyan; Marzuki, Marzuki (Tarbawi, 2018)
Some behaviors that deviate from students are already at a very alarming level, bad or deviant behavior from students is very troubling and can change the personality and identity of students, these people are left and difficulties in tackling torture behavior and morals of students will have a negative impact on the environment the student itself. Seeing various behaviors that arise regarding the behavior and morals of students so far, as well as discussing the learning process in schools, as a form of effort to cultivate personality, morality, and knowledge towards students, the roles that are greater than the delivery of education in schools, especially teacher as leader in class, success or failure Character education instilled in students is very dependent on the ability of teachers to manage the learning process in school. For this reason, the researchers wanted to know, study and analyze character education in schools, and also the readiness of teachers for education in schools, which would compare the readiness of teachers in management of education in public schools with special religious schools (Madrasa). The analysis uses inference analysis, namely analysis with simple regression techniques. From this study it was found that management of education has an influence on student morals, and also the ability and morals of students towards student learning in school. Thus, it can be said that the management of character education carried out in schools will be borne and the morals of students, this will be related to student achievement itself. Keywords. Management, character education, school, madrasa, student achievement.